2020
DOI: 10.3389/fvets.2020.00552
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Self-Esteem Between Cat Owners, Dog Owners, and Individuals Without Pets

Abstract: Introduction: Pet ownership may provide an additional source of social support and may contribute to the owner's self-esteem. Self-esteem is considered a basic human need and is associated with psychological conditions such as depressive symptoms. To date, there is limited knowledge on the association between keeping a pet and self-esteem. Objectives: The aim of this study was to determine whether cat owners, dog owners, and individuals without pets differ in terms of self-es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Consistent with results of this study, a study in Germany reported that people who were dog owners had higher self-esteem than persons without pets; in particular, male dog owners had higher self-esteem than men without cats or other pets [ 52 ]. Further, female cat owners had lower self-esteem than women without pets.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with results of this study, a study in Germany reported that people who were dog owners had higher self-esteem than persons without pets; in particular, male dog owners had higher self-esteem than men without cats or other pets [ 52 ]. Further, female cat owners had lower self-esteem than women without pets.…”
Section: Discussionsupporting
confidence: 88%
“…The findings from the evaluation questionnaire hint toward a perceived effect of peer support by the dog on the overall health of the owner. This effect was expected due to the increased perceived social support of the dog (the weight loss partner) (13,26) and the increased physical activity (12,27). The perceived responsibility increased for both the owner and the dog during the trials, which could provide increased motivation for a long term weight loss plan.…”
Section: Discussionmentioning
confidence: 98%
“…Beyond the obvious explanation that dogs simply need to be walked and hence stimulate physical activity, researchers have proposed that positive health effects for dog owners also result from the commitment of the owner to the dog (12), as well as increased perceived social support (11). Indeed, dogs are typically considered an important source of social support (13), which could benefit overweight people, as social support is known to positively affect weight loss attempts (14). Mutual benefits can be suggested, as in a previous weight loss study in people and pets, dogs got more exercise due to their owners' active weight loss program (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although the collective body of research has produced mixed evidence for the benefits of HAI, it is not surprising, given the potential benefits outlined above, that some studies link pet ownership and aspects of HAI (e.g., attachment, bonds, caretaking) with stress reduction [ 140 , 141 , 142 , 143 ], greater physical activity and overall better physical health [ 144 , 145 , 146 , 147 , 148 , 149 ], and higher levels of self-esteem and self-efficacy [ 148 , 150 , 151 ] at multiple stages of human development. In addition, there is some evidence that short-term HAI via animal-assisted activities and interventions may reduce the risk of, and symptoms of, specific adult mental health problems, such as anxiety [ 152 , 153 ] and depression [ 154 , 155 ].…”
Section: Social Relationships the Stress Response And Perinatal Mental Healthmentioning
confidence: 99%